2017
DOI: 10.1186/s40100-017-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and total factor productivity changes in European dairy farm sectors

Abstract: This paper aims to evaluate the technical efficiency and the total factor productivity change of dairy farms in EU countries. Analyses were carried out in order to determine which countries showed the best performance adaptations when the quota regime was relaxed and to evaluate the technical conditions of European farmers at the starting point of the new regime (milk quota abolition). A data envelopment analysis (DEA) was applied on aggregate data related to 22 European countries for the period from 2004 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 28 publications
1
56
2
3
Order By: Relevance
“…They found that the productivity of dairy processing industry has moderate growth, mainly driven by technical progress. The European dairy farms, which was analyzed by Madau, Furesi, and Pulina [11], were discovered the total factor productivity (TFP) change and a decline in productivity in the European milk industry. Tatli and Bayrak [12] explored the TFP change of 22 listed companies in Istanbul stock exchange (BIST) between 2011 to 2015 by applying the Malmquist index to data with input-oriented models.…”
Section: Literature Review On Malmquist Total Factor Productivity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the productivity of dairy processing industry has moderate growth, mainly driven by technical progress. The European dairy farms, which was analyzed by Madau, Furesi, and Pulina [11], were discovered the total factor productivity (TFP) change and a decline in productivity in the European milk industry. Tatli and Bayrak [12] explored the TFP change of 22 listed companies in Istanbul stock exchange (BIST) between 2011 to 2015 by applying the Malmquist index to data with input-oriented models.…”
Section: Literature Review On Malmquist Total Factor Productivity Indexmentioning
confidence: 99%
“…The nine self-owned stores (DMU 2,3,4,9,10,11,16,18,and 20) located in the fourth quadrant have a certain level of total factor productivity change, but there are areas where the current operation performance needs to be improved. From the perspective of operating performance, the self-owned stores located in this region can further adjust their operating efficiency, and over time, they will be further promoted to be competitive and have technical progress advantages.…”
mentioning
confidence: 99%
“…The empirical results, obtained by mean of Data Envelopment Analysis (DEA) in the period from 2004 to 2012, suggest that dairy farms have small scope for improving efficiency using their own technical input and that the sector has faced a decline in productivity. Madau et al (2017) conclude that factors other than efficiency can play a greater role in affecting farmers productivity and profitability in the near future. They also discuss about the change of the CAP needed to fit the new and more competitive dairy market scenario.…”
Section: Reportmentioning
confidence: 99%
“…Hence, the current EU sugar market seems far from reaching efficiency even if they conclude that the reform might have created more favorable conditions to improve it. Madau, Furesi and Pulina (2017) look at another very relevant farm sector that has also been affected by a policy change (i.e., the abolition of the quota system): the dairy industry. They assess changes in technical efficiency and total factor productivity in a large set of EU MS in order to determine which of these countries showed the best performance adaptations during the quota regime phasing out.…”
Section: Reportmentioning
confidence: 99%
“…However, these latter scholars have argued as the level of specialization in dairy farms has implied the highest level of efficiency in farms. Most recent studies aimed at investigating by a quantitative method the technical efficiency in all European Union countries using the FADN dataset have emphasized an increase of technical efficiency in Irish farms and also in other countries (Madau et al, 2017). Using the Data Envelopment Analysis method in farms belonging to the FADN, findings have pointed out as the technical efficiency correlates with the level of subsides disbursed by the European Union and with the level of land capital endowment corroborating the existence of a direct nexus between the variable farm size and technical efficiency (Zhu and Lansink, 2010).…”
Section: Introductionmentioning
confidence: 99%